Stunting incidence factors based on environmental health and economic status perspectives: A narrative review - Astuti, Dewi (Journal of Evidence-based Nursing and Public Health, 2026)
Background: Stunting is when a child's height or length is shorter than their age due to chronic malnutrition and repeated infections occurring during the first 1,000 days of life. According to data from the Ministry of Health, Indonesia's stunting rate was 19.8% in 2024, despite the Indonesian government's target of reducing stunting prevalence by 14% by that year. The persistently high prevalence of stunting has profound implications for the Indonesian nation. This study examines the factors contributing to stunting from the perspective of environmental health and economic status in Indonesia. Methods: This study used a narrative literature review on method based on previous studies sourced from PubMed, Scopus, Google Scholar, Science Direct, and MEDLINE published from January 2021 to October 2025, as well as reports on the results of the SSGI and SKI data from 2021 to 2024. Findings: This study focuses on the multifactorial causes of stunting related to Indonesia's environmental health and economic status. The availability of clean water, inadequate sanitation and latrines, and low economic conditions can cause stunting. Stunting requires a multisectoral strategy focusing on maternal and child nutrition, environmental health, and improving economic status. Conclusion: The evidence presented could guide policy development strategies and targeted interventions to prevent stunting, especially from an environmental health perspective, and improve economic status to prevent stunting in Indonesia. Novelty/Originality of this article: This study highlights the relationship between stunting incidence factors based on an environmental health and economic status perspective in Indonesia. The narrative review offers a holistic perspective in understanding the complexity of stunting factors and designing more effective intervention strategy policies and guidelines.